- Thread starter
- #1

Prove the following logic property using a

x + y * z = (x + y)(x + z)

Distributive Property?

Truth table.

By truth table I get: \(\displaystyle \bar{x}yz + x\bar{y}z + xyz\) which becomes z + z + xyz ?

Am I doing this wrong? Why am I not getting x + yz?

should I use algebraic manipulation?

x + yz = (x + y)(x + z)

x + yz = xx + xz + xy + yz

x + yz = x + xz + xy + yz

now what?

**Truth Table**(*perfect induction*). What is this property called?x + y * z = (x + y)(x + z)

*My Answer:*Distributive Property?

Truth table.

x y z f

[0]0 0 0 0

[1]0 0 1 0

[2]0 1 0 0

[3]0 1 1 1

[4]1 0 0 0

[5]1 0 1 1

[6]1 1 0 0

[7]1 1 1 1

By truth table I get: \(\displaystyle \bar{x}yz + x\bar{y}z + xyz\) which becomes z + z + xyz ?

Am I doing this wrong? Why am I not getting x + yz?

should I use algebraic manipulation?

x + yz = (x + y)(x + z)

x + yz = xx + xz + xy + yz

x + yz = x + xz + xy + yz

now what?

Last edited: